Salinity influences disease-induced mortality of the oyster Crassostrea gigas and infectivity of the ostreid herpesvirus 1 (OsHV-1) - Fuhrmann, Marine; Petton, Bruno; Quillien, Virgile; Faury, Nicole; Morga, Benjamin; Pernet, Fabrice (Aquaculture Environment Interactions, 2016)
Mortality of young Pacific oysters Crassostrea gigas associated with the ostreid herpesvirus 1 (OsHV-1) is occurring worldwide. Here, we examined for the first time the effect of salinity on OsHV-1 transmission and disease-related mortality of C. gigas, as well as salinity-related effects on the pathogen itself. To obtain donors for OsHV-1 transmission, we transferred laboratory-raised oysters to an estuary during a disease outbreak and then back to the laboratory. Oysters that tested OsHV-1 positive were placed in seawater tanks (35‰, 21°C). Water from these tanks was used to infect naïve oysters in 2 experimental setups: (1) oysters acclimated or non-acclimated to a salinity of 10, 15, 25 and 35‰ and (2) oysters acclimated to a salinity of 25‰; the latter were exposed to OsHV-1 water diluted to a salinity of 10 or 25‰. The survival of oysters exposed to OsHV-1 water and acclimated to a salinity of 10‰ was >95%, compared to only 43 to 73% survival in oysters acclimated to higher salinities (Expt 1), reflecting differences in the levels of OsHV-1 DNA and viral gene expression (Expts 1 and 2). However, the survival of their non-acclimated counterparts was only 23% (Expt 2), and the levels of OsHV-1 DNA and the expression of 4 viral genes were low (Expt 1). Thus, OsHV-1 may not have been the ultimate cause of mortality in non-acclimated oysters weakened by a salinity shock. It appears that reducing disease risk by means of low salinity is unlikely in the field.